ANALISIS PENGELOLAAN KEUANGAN DESA GUNA MENCEGAH KECURANGAN AKUNTANSI (ACCOUNTING FRAUD ) - Luh Dina Ekasari; Ahmad Mukoffi; Felagiana Tato; Johanis Nifanngeljau (Jurnal Akuntansi Trisakti, 2021)
Transfer income to Kucur Village, namely the Village Fund of Rp. 975,736,000 Village Fund Allocation of Rp. 524. 923,600 and the sharing of taxes and levies of Rp. 4,146,000 All are accountable by village officials through administration, reports, and accountability. The research objective was to supervise village financial management to prevent accounting fraud as measured by Permendagri No. 113 of 2014. Researchers researched the Kucur Village office, Dau District, Malang Regency, using a qualitative research type with a descriptive approach and the data used were primary and secondary data. , analyzing data using interviews and documentation, analyzing data using interactive model analysis and analysis techniques focus on administration, reporting, and accountability. The results of the Kucur Village financial research have been effective, it can be seen from the administration, reporting, and accountability, all village cash receipts, and village cash expenditures directly use the application of the side, by using the village financial management sides it is difficult to manipulate.